Impact of lifestyle factors and dietary patterns on serum uric acid levels and disease activity in gout: a systematic review - Mohammad Mustafa; Shahad Alshamrani; Lama Alghamdi; Hala Danish; Dana Alamoudi; Ghala Alshamrani; Abdullah Alagha; Adnan Alshaikh; Saher Alqarni; Yasser Bawazir (Journal of Health, Population and Nutrition)
Abstract Background Gout is a common type of inflammatory arthritis caused by monosodium urate (MSU) crystal deposition in the joints. This leads to pain, swelling, and restricted motion. Although pharmacological treatments are effective, lifestyle and dietary factors play crucial roles in managing gout and its flares. Aim This systematic review aimed to assess the effect of lifestyle factors, physical activity, and dietary patterns on serum uric acid levels and gout activity. Methods A search of PubMed, BMJ journals, and Google Scholar identified eight studies (five prospective cohort studies, two case-cross-over studies, and one randomized controlled trial), involving 47,879 participants (predominantly males [78.5–95.3%], aged 55–66 years). Eligible studies focused on adults with gout and examined the lifestyle or dietary factors affecting uric acid levels or gout activity. The review followed a pre-specified protocol (PROSPERO registration CRD42024594359). To optimize the quality, the bias risk was assessed using the Newcastle-Ottawa scale for observational studies and the Cochrane Risk of Bias 1.0 tool for randomized controlled trials. Results The findings suggest that consuming polyunsaturated fatty acid-rich fish, regular physical activity, and increased vegetable intake may reduce gout flares. Conversely, high purine intake (especially animal sources), excessive alcohol consumption, and obesity are risk factors for gout exacerbation. Some studies have reported reduced serum uric acid levels with dietary changes, whereas others have found no significant effect. Despite the variability and recall bias, dietary and lifestyle modifications may help manage gout and reduce disease activity. Conclusion The findings of this systematic review emphasize the importance of dietary and lifestyle factors in managing serum uric acid levels and reducing the risk of gout flares. Further research is required to establish clinical recommendations to improve patient outcomes.